2018
DOI: 10.2174/1874944501811010376
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Risk Factors Associated with Low Birth Weight in Indonesia

Abstract: Background: Low birth weight (LBW) is a major risk factor for death and disease in the fetus and newborn infant. However, the study about LBW and maternal risk factors involved in Indonesia is still limited. Objective: The present study attempted to examine the association of maternal risk factors including mother’s age, mother and husband education, mother and husband occupation and wealth, ANC visit, desired pregnan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
25
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 23 publications
4
25
0
6
Order By: Relevance
“…Multiple studies shows that birth weight of babies was influenced significantly by the number of antenatal checkups made by mother. 9,10,13,[15][16][17] In this study we also found statistically significant association of poor antenatal checkups with LBW (p = 0.004).…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Multiple studies shows that birth weight of babies was influenced significantly by the number of antenatal checkups made by mother. 9,10,13,[15][16][17] In this study we also found statistically significant association of poor antenatal checkups with LBW (p = 0.004).…”
Section: Discussionsupporting
confidence: 68%
“…10 Various studies done, for example, by Badshah et al, Swarnalatha et al, Agarwal et al, Yadav et al, Anjum et al, Agrawal et al, Siramaneerat et al all showed significant association between maternal educational level and LBW. 5,9,11,[13][14][15][16] But different studies also showed no association between residency and LBW. 11,13 Our study showed significant association between residence of mother with LBW (p = 0.017).…”
Section: Discussionmentioning
confidence: 99%
“…ANC provides routine monitoring of height and weight gain, identification of maternal or fetal medical problems, counseling on tobacco or substance use, providing psychosocial support, nutritional advice, and early intervention that can reduce adverse pregnancy output including LBW. Access to high-quality ANC should be emphasized as it not only improves maternal health but also provides opportunities for counseling and other risk assessment related to pregnancy 7 Unlike Indonesia, in Ghana, the local government recommends ANC visits. during pregnancy for 8 times.…”
Section: Discussionmentioning
confidence: 99%
“…In general, LBW describes maternal health conditions, maternal malnutrition, irregular access to ANC services, and the mother's low socioeconomic status 5,7,8 . Several studies explain that the factors that cause LBW include maternal factors, nutritional factors, social factors, medical factors, environmental factors, and socio-cultural factors 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Cases of morbidity and mortality include infectious disease, stunted in childhood period and underweight are common in LBW babies. 8 With the above background, this study was undertaken to determine the magnitude, risk factors and outcome of LBW babies to elaborate proper strategies to improve the survival of LBW babies.…”
Section: Introductionmentioning
confidence: 99%